Kepemimpinan Transformasional Dan Manajemen Mutu Dalam Meningkatkan Kinerja Lembaga Pendidikan - Syarif, Mohammad Nabil; Sunhaji, Sunhaji (JURNAL MANAJEMEN PENDIDIKAN, 2025)
This study aimed to analyze the influence of transformational leadership and quality management on improving the performance of educational institutions. The method used was qualitative research with a case study approach in several educational institutions that have implemented transformational leadership and quality management systems. Data were collected through in-depth interviews, observations, and documentation. The results showed that transformational leadership applied by principals was able to create a positive organizational culture, increase teacher and staff motivation, and encourage innovation in the learning process. The systematic implementation of quality management contributed to increased operational effectiveness and achievement of educational quality standards. The combination of these two factors resulted in significant institutional performance improvements, reflected in increased student academic achievement, stakeholder satisfaction, and institutional accreditation. The conclusion of this study indicated that the synergy between transformational leadership and quality management was the key to success in improving the performance of educational institutions in the current competitive era.